Effect of time in hardness test on artificially demineralized human dental enamel - Mirian de Waele Souchois Marsillac; Alberto Carlos Botazzo Delbem; Ricardo de Sousa Vieira (Universidade Estadual de Campinas, 2016)
A cross-sectional microhardness (CSMH) test was carried out in human dental enamel exposed to a demineralizing solution in order to evaluate two different times of indentation in sound tissue and artificially induced caries. Twenty caries-free extracted human molars had one of their smooth surfaces sectioned and the enamel surface was isolated with nail polish except for an area of 6 mm2 . These specimens were submitted to artificially induced enamel caries on a lactate buffer containing 0.1 ppm fluoride (F) during 28 days. All specimens were bisected to create groups A and B in which CSMH test was performed employing a Knoop indenter with a 25 g load for 5 or 10 s, respectively. Student's paired t-test (p<0.05) was used to determine statistically significant differences between groups A and B in 7 depths. There were no significant differences between any of the analyzed depths. Since the present experiment showed no significant difference when comparing indentations made with a 25 g load during either 5 or 10 s in different depths, this method can be used with either one of the time intervals tested without compromising a CSMH test on artificially demineralized human enamel.